Crystal structure and Hirshfeld-surface analysis of the pesticide etoxazole - Chaluvarangaiah Sowbhagya; Thaluru M. Mohan Kumar; Hemmige S. Yathirajan; Sean Parkin (Acta Crystallographica Section E: Crystallographic Communications)
Etoxazole (C21H23F2NO2), systematic name 4-(4-tert-butyl-2-ethoxyphenyl)-2-(2,6-difluorophenyl)-4,5-dihydro-1,3-oxazole, is a fluorinated insecticide and acaricide that inhibits chitin biosynthesis, disrupting insect development by preventing proper exoskeleton formation. Widely used in agriculture since 1998, it is readily absorbed by plant tissues and translocates within leaves. Metabolic studies have identified several oxidative degradation products, while toxicological assessments have examined potential effects, including oxidative stress. This study presents a detailed crystallographic and Hirshfeld surface analysis of etoxazole. The molecule consists of a central dihydro-oxazole ring flanked by 2,6-difluorophenyl and 4-tert-butyl-2-ethoxyphenyl groups, each twisted relative to the oxazole core. The dihydro-oxazole ring is nearly planar, with the substituted phenyl rings forming dihedral angles of 44.20 (4)° and 47.87 (4)° with the mean plane of the dihydro-oxazole. The ethoxy group exhibits a dihedral angle of 15.04 (11)° to the tert-butylphenyl ring, while the tert-butyl group itself shows minor torsional disorder [major:minor occupancies are 0.760 (6):0.240 (6)]. The molecular packing is dominated by van der Waals-type interactions, though weak C—H...F and C—H...O interactions lead to pleated layers parallel to the ab plane, which further stack along the c-axis direction. A Hirshfeld surface analysis confirms the prevalence of van der Waals interactions in crystal stabilization.